CONSERVING POSITIVE FACE-THREATENING ACTS IN THE ENGLISH TRANSLATION BUMI MANUSIA NOVEL - Susanto, Eko; Nababan, M.R; Santosa, Riyadi (Prosiding Seminar Nasional Bahasa Ibu, 2024)
This study aims to find the equivalent of Positive Face Threatening Acts (PFTA) accommodated in the English translation of the novel Bumi Manusia by Pramoedya Ananta Toer. In addition, this study also investigates the translation techniques and assesses the quality of the translation. The research method used is descriptive qualitative, which uses the dual data of PFTA in Indonesian and the translation of the novel. In analyzing the data, the researcher included the context parameters in pragmatics, namely Power, Distance, and imposition of Rank (P/D/R). The findings or results of the data analysis show two elements studied, namely PFTA equivalence and translation technique. Based on P/D/R parameters, there are seven contexts of PFTA equivalence analysis. Concerning Power, Distance, and imposition of Rank, there are indications that more actions aim to strengthen and enhance positive face-threatening acts in relationships with others and self-development.  In addition, the translation of Bumi Manusia shows a total of 983 frequencies which are divided into twelve types of translation techniques. The dominance of the most used English translation technique is the established equivalent technique with a percentage of 72.94% of the total data or frequency found. The translation quality of Bumi Manusia has a good level of accuracy, acceptability, and readability, with a score of 2.92 out of 3.